2019
DOI: 10.1111/jocn.15110
|View full text |Cite
|
Sign up to set email alerts
|

“It is still intense and not unambiguous.” Nurses' experiences in the euthanasia care process 15 years after legalisation

Abstract: Aims and objectivesTo explore how Flemish nurses working in hospitals and home care experience their involvement in the care of patients requesting euthanasia 15 years after the legalisation of euthanasia.BackgroundEuthanasia was legalised in Belgium in 2002. Despite prior research that charted the experiences of nurses in euthanasia care before and right after legalisation in Belgium, it remains unclear how Flemish nurses currently, 15 years after the legalisation, experience their involvement.DesignA grounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Recent qualitative studies have provided further evidence of nurses' experiences. A study of 26 Belgian nurses' experiences with euthanasia (Bellens, Debien, Claessens, Gastmans, & Dierckx de Casterle, 2019) revealed findings similar to an earlier study in the Belgian context (Denier, Dierckx de Casterle, De Bal, & Gastmans, 2010). Nurses experienced the euthanasia death as emotionally impactful.…”
Section: Introductionsupporting
confidence: 72%
“…Recent qualitative studies have provided further evidence of nurses' experiences. A study of 26 Belgian nurses' experiences with euthanasia (Bellens, Debien, Claessens, Gastmans, & Dierckx de Casterle, 2019) revealed findings similar to an earlier study in the Belgian context (Denier, Dierckx de Casterle, De Bal, & Gastmans, 2010). Nurses experienced the euthanasia death as emotionally impactful.…”
Section: Introductionsupporting
confidence: 72%
“…Even as some nurses described being grateful that they could fulfill patient wishes for a MAiD death, the death itself provoked emotions that could be uncomfortable or disturbing. Studies of nurses’ experiences with assisted death from Belgium ( Bellens et al, 2020 ; Denier, Gastmans, et al, 2010 ), the Netherlands ( Lewis, 2018 ; van de Scheur & van der Arend, 1998 ), and Canada ( Beuthin et al, 2018 ) have similarly described a range of emotions that nurses experience in the context of an assisted death. Furthermore, other authors have noted the same sense of gratitude nurses describe at being part of a care system that provides an opportunity to fulfill patients’ wishes and relieve their suffering ( Bruce & Beuthin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nurses from the Netherlands described their supportive role as demanding and nerve-wracking ( Lewis, 2018 ; van de Scheur & van der Arend, 1998 ). Nurses from Belgium described their role as intense, acknowledging that even though their comfort level develops over time, euthanasia is not something they become used to ( Bellens et al, 2020 ; Denier, Dierckx de Casterle, et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Consequently there is limited local data available to inform hospital approaches to implementation despite the shared goal of reducing suffering and providing good dying experiences for patients. 3,5,6 The experiences of clinicians in other jurisdictions have been mixed, with some experiencing considerable difficulties in working relationships, [7][8][9] whilst others found that relationships with colleagues could also be strengthened 7 . For some there was a lack of clarity in their role and scope of practice.…”
Section: Introductionmentioning
confidence: 99%
“…10 Many clinicians experienced complex emotions 9 including both profound feelings of professional fulfilment and emotional distress. 8 Professional bodies differ in their attitudes towards VAD. Objections and concerns have been outlined in the position statements of a number of groups including the Australian Medical Association which takes the position that doctors should not be involved in interventions that have the ending of a person's life as their primary intention.…”
Section: Introductionmentioning
confidence: 99%